Clima urbano e conforto térmico no município de Ourinhos - Souza, Débora Moreira de [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
The study of Geographical Climatology, particularly of the Urban Climatology, assumes importance in the development of urban planning, since it should encourage the integration of social and economic development, without detrimental the natural resources. Ourinhos, located in the southwesten of São Paulo state, Brazil, concentrates economic activities and consequently environmental problems as large urban centers. This study aims to monitor, identify, evaluate, characterize and understand the dynamics of the following weather variables: rainfall, temperature, relative humidity and wind (direction and speed). Also to calculate the water balance of the study area. Sought to understand how the elements and climatic factors in the region are related and its influence on the thermal sensation of the population. It was noted the existence of two climatological periods well defined in Ourinhos hot and humid in summer and other cool and dry in winter. It was also noted that according to different climatic regions analyzed the thermal discomfort in the city tends to cause effects on human health, on energy consumption and on labor income. In conclusion the climatic dynamic is extremely important in regional development, which should contribute directly to the life quality of this population.
Keywords: Clima - Ourinhos (SP); Conforto termico - Ourinhos (SP); Variáveis climáticas - Ourinhos (SP)